Cooperative Content Dissemination on Vehicle Networks - Luís Diogo Recharte Silva (2018)
Vehicular networks have seen great advancements over the last few years, mostly due to the increased eagerness for smart and autonomous vehicles that motivate hefty investments by the automotive industry. The absence of a timely and cost-effective way to perform over-the-air (OTA) updates is contributing to defer the deployment of large fleets of connected vehicles. There is a high cost associated with transmitting data over cellular networks and it cannot be expected that every vehicle has access to a station or depot with adequate connectivity where it can get the awaited data cheaply nor that this solution happens timely enough. With this in mind, this thesis presents the design and implementation of a cooperative content dissemination protocol that takes advantage of Vehicle-to-Vehicle (V2V) communication links to distribute data across a network with reduced costs. Moreover, this work is complemented with a performance analysis of the protocol on a deployed network of 25 vehicles.